WOMEN'S PERCEPTIONS OF THE SIGNS AND SYMPTOMS OF CLIMACTERIC ASSOCIATED WITH SEXUAL ACTIVITY - Silva, Camila Vitória Viana; do Nascimento, Layana Santos; da Costa, Arlete Rodrigues Chagas; Rodrigues, Ingridy Fátima Alves; Pinto, Solange de Paiva; de Albuquerque, Ageu Procópio Almeida; Mihaliuc, Domitília Bonfim de Macêdo; Teixeira, Leila Barbosa Rezende (Seven Editora, 2026)
Objective: To investigate women's perceptions of climacteric signs and symptoms associated with sexual activity at a Basic Health Unit in the Federal District.Method: This is a descriptive-exploratory study with a qualitative approach, conducted at a Basic Health Unit in the Federal District. Participants were 30 women aged 40 to 65 years, interviewed between February and April 2025. A semi-structured questionnaire containing sociodemographic data and open-ended questions about the physical and psychological changes of climacteric, sexuality, and the impact of symptoms on sex life was used. The interviews were analyzed using Bardin's Content Analysis.Results: Three categories emerged: physical and psychological aspects related to menopause; difficulties and challenges in the area of sexuality; and social repercussions and coping strategies adopted by women. Participants reported symptoms such as hot flashes, irritability, anxiety, vaginal dryness, and weight gain, which directly affected self-esteem, well-being, and sexuality. In the social sphere, changes in family and marital relationships were observed. As coping strategies, spiritual support, dialogue, and the use of herbal teas were highlighted.Final considerations: the findings demonstrated that menopause is experienced in a complex way, with profound repercussions on sexual activity, and the need for a more sensitive and comprehensive approach in Primary Health Care.